Cervical intraepithelial neoplasia grade 1 and long-term risk of progression and treatment - Ingrid Baasland; Tone Bjørge; Birgit Engesæter; Ameli Tropé; Signe Opdahl (PLoS ONE, 2025)
Background Cervical intraepithelial neoplasia grade 1 (CIN1) is often managed by active surveillance, as the risk of progression to high grade lesions is reported to be low, but long-term data is sparse. To inform management of CIN1, we estimated risk of progression and occurrence of treatment in women attending a cervical cancer screening program. Methods We used nationwide, registry data on all women aged 25–69 years attending the Norwegian Cervical Cancer Screening Program in 2002–2019. The eligible source population was women with at least one cytology registration (n = 1,771,876). Women with a histologically confirmed, first CIN1 diagnosis were included (n = 26,130) and followed for detection of CIN2+, defined as histologically confirmed CIN2, CIN3, adenocarcinoma in situ (AIS), or cervical cancer. CIN3+ was defined as CIN3, AIS, or cervical cancer. Treatment included both excision and ablation. Results Overall, the cumulative incidence of CIN2+ increased to 9.5% (95% confidence interval (CI), 8.8 to 9.5) during the first year and to 19.0% (95% CI, 18.4–19.5) during the first five years. For women with high-grade cytology, 5-year cumulative incidence reached 26.0% (95% CI, 25.0–27.0), whereas for women with normal or low-grade cytology, but HPV16 and/or HPV18 positive status, the corresponding estimate was 25.0% (95% CI, 23.3–26.8). Other high-risk HPV genotypes and HPV negative status were associated with lower risks (5-year cumulative incidence 15.5% (95% CI, 14.5–16.6) and 8.2% (95% CI, 7.1–9.5), respectively). Detection of CIN3+ was substantial (cumulative incidence 5.7% (95% CI, 5.4–6.0) and 12.7% (95% CI, 12.2–13.1) after 1 and 5 years, respectively), and overall, cumulative incidence of treatment was 15.2% (95% CI, 14.7–15.7) after 5 years, following similar patterns as observed for CIN2+. Conclusions A differentiation of follow-up guidelines by index cytology and HPV16/18 status for women diagnosed with CIN1, might be warranted.